Reforming higher education in the Nordic countries: studies of change in Denmark, Finland, Iceland, Norway and Sweden - UNESCO. IIEP; Fägerlind, Ingemar; Strömqvist, Görel (UNESCO-IIEP, 2004)
Incl. graphs, and bibl. references This book is concerned with how the systems of higher education have changed in the Nordic countries over the past two decades in response to multiple demands, which include expansion, diversification, accountability, quality control, internationalization and globalization.Internationally there is an interest in how Denmark, Finland, Iceland, Norway and Sweden have handled such demands, at the same time as experiencing fiscal pressures, and striving to maintain quality and increase equity. Within the Nordic countries, policies and reforms in higher education are the subject of much debate.The study examines the role of the market and the state in the five Nordic countries, as higher education and research are regarded as important political tools in the development of national and regional economies. An overview and analysis of recent changes in the systems of higher education is provided in the light of global and European developments. Finally, the book looks at how the different countries consider the tradition of lifelong education, the barriers between university and non-university institutions and the participation in higher education by men and women.